PENGGUNAAN MINYAK SAFFLOWER (Carthamus tinctorius L) DAN INOSITOL TERHADAP KADAR AIR DAN KEEMPUKAN DAGING AYAM SENTUL JANTAN - Ziya Auliya Wardaya; Ismoyowati Ismoyowati; Elly Tugiyanti (ANGON: Journal of Animal Science and Technology, 2020)
Background. “Using Safflower oil and inositol on water content and tenderness meat of Sentul Chicken”. The purpose of the research was to know the effect of using safflower oil and inositol into feed to water content and tenderness meat of Sentul Chicken. The research was held in February 5th until May 30th 2020 in Experimental Farm, Nutrition Science Laboratory and livestock product technology, Animal Science Faculty, Jenderal Soedirman University, Purwokerto. Materials and Methods. The material of research that used in this research was male Sentul chicken aged 4 weeks and totalled 81 chickens that maintained for 8 weeks. The material research used safflower oil and inositol. The research used a completely randomized design (CRD) in nine treatments and three repetitions, in each repetition consists of 4 male chickens. Variable be measured in this study were water content and tenderness meat of Sentul Chicken. The data obtained were analyzed using analysis of variance. The treatments are R0 = Basal feed (0% safflower oil and 0% inositol) ; R1 = Basal feed + safflower oil 0,5% ; R2 = Basal feed + safflower oil 1,0% ; R3 = Basal feed + Inositol 0,5 % ; R4 = Basal feed + Inositol 1,0 % ; R5 = Basal feed + safflower oil 0,5% + inositol 0,5% ; R6 = Basal feed + safflower oil 0,5% + inositol 1,0% ; R7 = Basal feed + safflower oil 1,0% + inositol 0,5% ; R8 = Basal feed + safflower oil 1,0% + inositol 1,0%. Results. The result of the analysis of variance showed that the use of safflower oil and inositol had no significant effect on water content and tenderness meat of sentul chicken. The average of water content of sentul chicken meat was 72,77% ± 2,76 until 75,11% ± 1,68. The average of tenderness of sentul chicken meat around 0,05 mm/g/t sampai dengan 0,07 mm/g/t. Conclusion. The conclusion of this study is the using of safflower oil and inositol maintained the water content and tenderness meat of sentul chicken.